Production plan scheduling on electronic factory - Thepparit Sinthamrongruk (2019)
© 2019 IEEE. Production scheduling is essential in the modern manufacturing system. ARENA simulation software is generally used in the industrial practice to simulate discrete events for production. This paper aims to optimise the production sequence for the electronic assembly factory. In this study, we proposed an approach that enables collaboration between the software simulation and the optimisation theory. The structure is designed based on the hierarchical approach which divides the system into two layers: ARENA simulation software is used for simulating the production events while five optimisation algorithms consisting of Palmer, Gupta, CDS, FMECA and genetic algorithms are employed as the optimiser. The advantage of the proposed approach is that developers can program the algorithms to explore the optimal solution with the existing high reliable simulated model created by the planner/manager. A comparison of the performance between different algorithms with a real case study for the benchmark revealed that the GA explored a superior solution with minimising operational time or makespan compared to its rival techniques regarding for production. (167 words)